Cockney Cities - Cox, Jeffrey (Romanticism and Victorianism on the Net, 2011)
We normally associate writing about the city with a line of continental writers from Baudelaire to Benjamin and beyond. However, there was an earlier account of the city in the writers identified with the Cockney School and in particular Leigh Hunt. Hunt’s Wishing Cap Papers are a striking instance of an attempt to write about the city from the perspective of someone who is, on the one hand, below the circles that control the city, and, on the other hand, capable of imagining a world beyond the city as it exists in the present. While our image of Hunt in the city might begin and end with Dickens’ Skimpole, we can recover behind that savage portrait an engaged city-dweller trying to imagine the urban space remade by pleasure. This is part of the Cockney attempt to create a cosmopolitanism that moves from the local to the global in order to bypass the nation.